DEVELOPING CRITICAL THINKING SKILLS AND DIGITAL SKILLS LITERACY THROUGH SOCIAL MEDIA: AN INNOVATIVE APPROACH TO EDUCATION - Paola Alejandra Trujillo Amezquita; Edwin Fernando Guarín Parra (LÍNEA IMAGINARIA, 2025)
This scientific essay investigated the potential of social networks (RR. SS.) as pedagogical tools for the development of critical thinking (CP) and digital literacy (DL) in the Colombian educational system, considering its normative framework. Methodologically, a documentary and argumentative analysis was used, examining learning theories such as connectivism, 21st century competencies, and the concept of digital citizenship. Key Colombian public policies and educational laws, such as Law 115/94 and the Ten-Year Education Plan 2016-2026, were reviewed and contrasted with the current context of technological access and pedagogical practices in the country. The results show that, although there are significant challenges in infrastructure and teacher training, the RR. SS. offer considerable potential to promote CP and DL. It was found that the mere availability of technology or the social use of social media by students does not guarantee the development of these competencies; strategic teacher mediation and a clear pedagogical intentionality are indispensable. The main conclusions underline that the effective integration of social media requires a paradigm shift towards educational practices that promote critical interaction with information and the creation of meaningful content. The strategy “Conectarte for Critical Digital Citizenship” is proposed, a comprehensive model that articulates teacher training, curricular adaptations, resource development and the promotion of an ethical and responsible digital culture, as a way to realize this educational potential in Colombia.